Performance of private companies involved in urban solid waste management: evidence from three cities in Ghana - Sampson Oduro-Kwarteng; Meine P. van Dijk (2008)
An assessment of performance of service providers involved in solid waste management was conducted to provide understanding of the performance drivers, constraints and challenges. A survey of 15 private companies was conducted in Accra, Tema and Kumasi to assess the solid waste vehicle productivity and utilisation, and the factors that influence vehicle productivity and utilisation. The vehicle productivity and utilisation of seven out of the 15 companies were below the average of 21 tonnes per day per vehicle and 61% respectively. The study suggests a non-linear relationship between utilisation and size of company. The performance implications are that companies with less than 15 vehicles will perform better in terms of vehicle productivity and utilisation than those with more than 15 vehicles. The factors that seem to influence the performance are route planning, supervision of vehicle operations and maintenance.